Toxicidade de inseticidas para abelhas nativas brasileiras - Pereira, Aurélio de Souza (2023)
The presence of xenobiotics in the environment represents a great risk for several species of beneficial organisms and, when it comes to Brazil, there is an immense diversity when we talk about bees. Among the insecticides used to control various insect pests, there are molecules from the organophosphate groups (dimethoate), neonicotinoid (thiamethoxam), pyrethroid (deltamethrin) and phenylpyrazole (fipronil), neurotoxic products widely used in agriculture, such as crops of cotton and apple. With regard to bee species, we can highlight the largest group of native Brazilian bee species, the Meliponini tribe, fundamental in the pollination of native angiosperms and in the development of meliponiculture, the activity responsible for managing these species. Highlighting the species Tetragonisca angustula, Scaptotrigona xanthotricha and Frieseomelitta varia, present in the meliponary of the Federal University of Lavras. This comparative study aimed to carry out the exposure of these three species of bees to the insecticides deltamethrin, dimethoate, fipronil and thiamethoxam in laboratory conditions. The results obtained at a lethal dose of 50 (LD50) demonstrate the existence of a differentiated response to intoxication with the same molecules studied with the Apis mellifera bee species, justifying the need for further studies with this group of native insects, aiming the development of protocols protection.